THE PERFORMANCE OF PATRIARCH JOSIFF IN THE EYES OF A GRECO CATHOLIC FROM POLAND - ROSA, Robert (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
The aim of the author of this article is to present some personal reflections on the personality of Patriarch Josyf Slipyj. Although the author never had the opportunity to meet Patriarch Josyf personally, his influence on the environment and the Greek Catholic community in Poland was indeed significant. Analysing the time of his youth, which in the author's case coincided with the end of the communist regime in Poland and the emergence of «Solidarity», he points out from his own experience that these people had a great influence on the formation of his national and ecclesiastical identity, as well as on the formation of his vocation to the priesthood, his decision to enter the Lublin Theological Seminary. Patriarch Josyf Slipyj's unwavering stance against the totalitarian system was an inspiration to the young generation of Greek Catholics in Poland in the 1980s. Undoubtedly, Patriarch Josyf's actions and initiatives provided strong impulses for exploration in the fields of faith and science, and this area probably requires in-depth research. Perhaps one can venture to say that this witness of faith continually «invites» people whose fathers or grandfathers lost their homeland as a result of the 1947 Operation «Wisla» to search for their identity. Influenced by assimilation processes and standing on the threshold of adulthood, young Ukrainians in Poland sooner or later have to answer fundamental questions: who am I and how do I believe? To which church and national community do I belong? Are the values of my ancestors close to me? Some will undoubtedly get lost and remain forever at the crossroads, but the majority, I hope, will make the effort to rediscover the tradition of Eastern Christianity and the tradition of their national culture, and thus deepen or rekindle their faith, which is the faith that every nation lives by on its historical path. These issues remain relevant, and in the current experience of the armed onslaught in Ukraine, refugees and migration also apply to those people who, due to economic conditions and the effects of war, are forced to leave their Нomeland.